Infancia y ciudadanía: El orden generacional del Estado de Bienestar - Wintersberger, Helmut (Política y Sociedad, 2006)
The concept of children’s citizenship in modern society emerges from 2 major achievements of the late 20th century: the development of an authentic sociological debate on childhood (new childhood studies) and the adoption and increasing implementation of the UN-Convention on the Rights of the Child. In the following paper an attempt is being made to combine these two discourses around the problem of generational distributive justice. In the first section 2 shifts are being addressed by which modern childhood has been shaped: a change of the generation contract which, at the level of the household, made children redundant as assets for social security in old age, and a change of the generational division of labour usually referred to as scholarisation of childhood. The other three sections are about generational justice (and disparities). This topic is dealt with at various levels: the semantic and theoretical level, the pragmatic level of facts figures and policies, but also the methodological level of measuring child poverty and the generational distribution of resources. First comes a more general plea for enlarging welfare state analysis by the generational dimension. This is followed up by a conceptual clarification of absolute, relative and generational child poverty, as well as of a short review of reasons, risks and remedies with a view to child poverty. The final section is dedicated to the UN-Convention on the Rights of the Child, in particular its definition of a decent standard of living for children.
Keywords: Childhood; Welfare state; Generational distributive justice; Child poverty; Childrens rights